Computer modeling of water distribution systems - Robinson, Laredo (AWWA manual ;, 2012)
Modeling lets designers predict the performance of water distribution systems to solve a wide variety of design, operational, and water quality problems. This Manual provides distribution engineers and operators with information on developing and using computer hydraulic models of water distribution systems. Chapters take the reader from basics through data collection, model design, calibration, and applications. The Third Edition provides new information on hydraulic calibration, transient analysis, and modeling storage tank mixing and water age.